Bankruptcy among young users of credit card in Malaysia : a case study of RHB islamic (Menara Yayasan Tun Razak) bank customers. - Zaminor Zamzamir@Zamzamin; Azila Jaini; Siti Zamanira Mat Zaib (Faculty of Entrepreneurship and Business,UMK, 2015)
Young users nowadays holding a numbers of Credit Card and it become a normal scenario right now. Some people claims that by having a numbers of credit cards, it will reflect someone socio economy status. Without realizing the impact of the excess usage of credit card young users were declaring bankrupt due to credit card debts. This paper reviews the bankruptcy among young users of credit card in Malaysia. The results disclose that the compulsive spending is more influenced towards the factors that lead to bankruptcy in the early age among credit card user.